Sustainability and beyond: decoding the influences of corporate social responsibility on employer brand attractiveness - Greta Gintale; Ricardo Correia; Dominyka Venciute; Ruta Lapinskiene (Cogent Business & Management, 2024)
This research explores the complex relationship between perceived corporate social responsibility (CSR), sustainability self-identity and generational differences, focusing on their influence on employer brand attractiveness. Recognizing CSR's critical role in talent acquisition, the study examines the impact of philanthropic, ethical and environmental CSR activities on employer brand perception. While environmental and philanthropic CSR significantly improve employer attractiveness, ethical CSR shows a less substantial impact. The research also introduces sustainability self-identity as a possible moderating factor, investigating whether individuals whose values align with CSR perceive employer brands differently. Contrary to what was expected., sustainability self-identity does not significantly moderate this relationship. Additionally, the study explores generational differences, revealing that interest in CSR is consistent across age groups, challenging stereotypes about generational preferences. Notably, Baby Boomers and Generation Z demonstrate similar engagement with CSR as Generation X and Millennials. The findings suggest that organizations should focus on environmental and philanthropic initiatives to strengthen their employer brand. Furthermore, the study highlights the broad appeal of CSR initiatives across generational lines, paving the way for future research on the interplay between CSR, employer attractiveness and individual and generational dynamics.
Keywords: 650; CSR (corporate social responsibility); employer brand attractiveness; sustainability self-identity; generational differences; philanthropic CSR; ethical CSR; environmental CS